Sustainable Supply Chain Management Practices in Ghana - Johnson NSOWAH; Maxwell PHIRI A. (Indonesia Strategic Sustainability, 2023)
The study assessed the sustainable supply chain management (SSCM) practices of 303 manufacturing firms in Ghana with an annual turnover of not less than 1,000,000, which were purposively selected for the study. A questionnaire comprising closed-ended questions was used to collect data on the SSCM practices of the firms, which were sustainable product design (SPD), sustainable process design (SP), supply-side collaboration (SSC) and demand-side collaboration (DSC). A weighted average index was used for the data analysis the results of which revealed that in manufacturing firms under study, SPD had a mean score of 4.44, SP had a mean score of 4.48, SSC had a mean score of 4.52 and DSC had a mean score of 4.52. The study identified many issues policymakers should look at to promote SSCM practices in manufacturing firms. In addition, policies should prioritise energy/material consumption; the reusing, recycling and recovering of materials; a standardised product design to facilitate reuse; environmentally-friendly materials, products and manufacturing processes; the easy disassembly of materials products; product life cycle analysis; and the formalisation of procedures for environmentally-friendly product design. Based on the diminishing of the world’s natural resources and the importance of SSCM, it is recommended that all manufacturing firms in Ghana and the world adopt SSCM practices. Moreover, manufacturing firms need to collaborate with their customers to anticipate and solve sustainability problems to achieve sustainability goals.